Servant Leadership and Work Performance: The Mediating Roles of Knowledge Sharing and Burnout and the Moderating Role of Innovative Culture among Civil Servants of the Bima Regency Government - Jeki Julkarnain; Qurrotul Aini, Intan Novela (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of servant leadership on work performance among civil servants of the Bima Regency Government, with knowledge sharing and burnout as mediating variables and innovative culture as a moderating variable. Primary data from 220 respondents, selected through convenience sampling, were analyzed using PLS-SEM with SmartPLS 3. Servant leadership has a positive and significant effect on work performance and knowledge sharing, but not on burnout. Knowledge sharing positively and burnout negatively affect work performance. Knowledge sharing partially mediates the servant leadership–performance relationship, burnout does not, and innovative culture strengthens it as a quasi-moderator.